Dinamika Kelembagaan Desa: Gampong Era Otonomi Khusus Aceh - Irine Hiraswari Gayatri (Pusat Penelitian Politik, 2008)
Study on the evolution of local traditional village governance in Aceh called gampong which conducted in Aceh Utara and Bener Meriah districts of Nanggroe Aceh Darussalam province explores the transformation of roles functions its meanings as well as efforts to revitalise them The findings show such transformation has been heavily influenced by changing political economy and social contexts that occur in Aceh and or through central government regulations.